EVALUASI KAPASITAS TERMINAL 3 PENUMPANG BANDAR UDARA INTERNASIONAL SOEKARNOHATTA - , MOHAMMAD ICHSAN LUTFI; , Ir. H. Wardhani Sartono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Soekarno-Hatta International Airport is one of collector airport or hub of the 12 airports managed by PT. Angkasa Pura II. According to the Director General and Personnel PT Angkasa Pura II Endang Sumiarsa, Airports Council International noted that the number of passengers who crowded Soekarno Hatta International Airport in 2012 has reached 57 million passengers from 49 million passengers in 2011 and 44 million passengers in 2010. While the ideal of its capacity 22 million passengers. In order to support the movement of passengers that exist today, it is necessary to study the passenger terminal of the airport to find the development needs to be planned for later executed. This evaluation was aimed to evaluate the capacity and needs of existing passanger terminal by JICA guidelines and IATA based on number of peak hour passengers served by the current year and other secondary data up to the next 10 years which in 2023 based on the data owned by PT. Angkasa Pura II. To estimate the number of annual passengers by the year 2023 used a method of percent increase in the mean. Based on calculations by JICA, the area of Terminal 3 is 18.818 m2 while the factual area is 34.488 m2 so the passanger terminal is able to serve the number of existing passengers. Meanwhile, according to calculations based on IATA standards produced that some facilities can not serve passenger peak hours, such as curbs departure and arrival, departure lobby, check-in counters, passport control set, baggage claim area, and baggage claim devices. Based on the estimated annual passenger movement with a growth rate of 10.56% per year, is expected to Terminal 3 Soekarno-Hatta International Airport will experience overcapacity in 2019 and in 2023 required 53.572 m2 of spacious terminal.